Embodiment in Cross-Linguistic Studies : The 'Foot/Leg' - Carvalho, Mateus Cruz Maciel de; Kraska-Szlenk, Iwona (Brill's Studies in Language, Cognition and Culture, 2026)
Over the past two decades, linguistic research into embodiment has paid considerable attention to the human body and its individual parts, particularly within typological and cognitively oriented studies. This volume continues that line of inquiry with a specific focus on the lower limb. It shows that, like other major body parts, the lower limb serves as a highly productive source domain for a wide range of conceptualisations across the world's languages and cultures. More generally, the book contributes to the growing body of work at the intersection of cognition, language, and culture. It also engages with embodiment theory, which posits that human cognition and language are fundamentally grounded in sensory-motor experience. Contributors are: Kelsie Pattillo, Jaime Peña, Gema Silva, Franklin Espinoza, Marleny Rodríguez, Małgorzata Waśniewska, Rosanna Tramutoli, Izabela Will, Joseph Jaoko Ochieng, Annika Tjuka, Cristina Martins Fargetti, Carmen Lúcia Reis Rodrigues, Judit Baranyiné Kóczy, Iwona Kraska-Szlenk, Yi Tie, Yongxian Luo, and Mateus Cruz Maciel de Carvalho.